Pengaruh Pernikahan Dini terhadap Tingkat Pertumbuhan Stunting di Kelurahan Terjun Kecamatan Medan Marelan - Dinda , Khadijah; Hanum, Khairunisa; Hasanah , Nadratul; Fazrah, Yasmi; Saleh, Syarbaini (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The purpose of this study was to determine the effect of early marriage on stunting growth rates in Kelurahan Terjun, Medan Marelan District. The research method used is an analytical observational method with a cross-sectional research design. From the results of this study, further research is still needed to overcome and prevent stunting events at the Waterfall Health Center, Medan Marelan District in order to create a stunting prevention program from its risk factors.